Shionone Relieves Urinary Tract Infections by Removing Bacteria from Bladder Epithelial Cells - Hao Yin; Jiaoli Zhu; Yi Jiang; Yijing Mao; Chenquan Tang; Hui Cao; Yufang Huang; Huijun Zhu; Jianping Luo; Qingjiang Jin; Qinglei Jin; Yi Xue; et al. (Cellular Microbiology)
In clinical practice, urinary tract infections (UTIs) are second only to respiratory infections in terms of infectious diseases. In recent years, drug resistance of Escherichia coli (E. coli) has increased significantly. The therapeutic effects of Shionone on UTI were assessed by modelling UTI in SD rats and SV-HUC-1 cells with E. coli solution. After treatment of Shionone, the UTI rat model showed a decrease in wet weight/body weight of bladder, as well as a reduction in cellular inflammatory infiltration of bladder tissue and a decrease in urinary levels of IL-6, IL-1β, and TNF-α. In addition, the levels of proinflammatory factors were significantly reduced in a dose-dependent manner in UTI cell model treated with different doses of Shionone (5, 10, and 20 μg/kg). The results of immunofluorescence analysis in both in vivo and in vitro experiments revealed that Shionone reduced bacterial load and the number of E. coli colonies growing on the plates was greatly reduced. These results suggested that Shionone has a good therapeutic effect on UTI, achieved by reducing bacterial load in bladder epithelial cells. The data presented here provide a basis for further research into the treatment of UTI.